U.S. policy failures and North Korean nuclear non-proliferation - John Bringe (2017)
Following the latest events of North Korea's fourth nuclear test in early 2016, North Korean nuclearization is an increasingly relevant issue. This has been an issue on U.S. radar since the early 1990's, but to date, little success has been achieved in efforts to curb nuclear proliferation on the Korean Peninsula. While North Korea holds much of the blame for proliferation and is a renegade state that is difficult to work with, this dissertation examines the domestic factors in the U.S. that have greatly impeded the success of efforts by the U.S. to denuclearize North Korea. The U.S., having a divided government, faces a domestic environment in which it is difficult to implement strong, consistent foreign policy in the face of criticism from the opposing party. This constant opposition between Democrats and Republicans leads to inconsistent policy toward North Korea that changes between and within administrations. This inconsistency creates a North Korea mistrustful of the U.S. and allows for it to pursue nuclear weapons more fervently. This has been a pattern since the beginning of the U.S. relationship with North Korea over nuclear weapons and continues to the present. If strong, consistent policy is not implemented with bipartisan agreement, North Korea cannot be the only party to blame and nuclear proliferation will continue on the Korean Peninsula.